Assessing the accuracy and educational value of YouTube videos on a novel regional anesthesia technique (PENG block) - Ebru Aladağ; Muhammed Emin Zora (PLoS ONE, 2026)
The Pericapsular Nerve Group (PENG) block is a novel regional anesthesia technique that provides adequate analgesia while preserving motor function. This cross-sectional study evaluated the quality, reliability, and educational value of YouTube videos on the PENG block. Thirty-six videos were analyzed using validated scoring systems (GQS, JAMA, DISCERN, and modified DISCERN). Overall video quality was moderate, with higher scores observed in procedural and institutional videos. The findings highlight both the educational potential and the need for quality control in online medical content.